High Performing Solid‐State Organic Electrochemical Transistors Enabled by Glycolated Polythiophene and Ion‐Gel Electrolyte with a Wide Operation Temperature Range from −50 to 110 °C. (7th November 2022) - Wu, Xihu; Chen, Shuai; Moser, Maximilian; Moudgil, Akshay; Griggs, Sophie; Marks, Adam; Li, Ting; McCulloch, Iain; Leong, Wei Lin
Abstract: The development of organic electrochemical transistors (OECTs) capable of maintaining their high amplification, fast transient speed, and operational stability in harsh environments will advance the growth of next‐generation wearable and biological electronics. In this study, a high‐performance solid‐state OECT (SSOECT) is successfully demonstrated, showing a recorded high transconductance of 220 ± 59 S cm −1, ultrafast device speed of ≈10 kHz with excellent operational stability over 10 000 switching cycles, and thermally stable under a wide temperature range from −50 to 110 °C. The developed SSOECTs are successfully used to detect low‐amplitude physiological signals, showing a high signal‐to‐noise‐ratio of 32.5 ± 2.1 dB. For the first time, the amplifying power of these SSOECTs is also retained and reliably shown to collect high‐quality electrophysiological signals even under harsh temperatures (−50 and 110 °C). The demonstration of high‐performing SSOECTs and its application in harsh environment are core steps toward their implementation in next‐generation wearable electronics and bioelectronics. Abstract : A solid‐state organic electrochemical transistor (SSOECT) with high amplification capability and ultra‐fast speed is realized by combining glycolated polythiophene and ion‐gel electrolyte. The amplifying power of the SSOECT can also be retained under extremely low and high temperatures, thus presenting the excellent potential of SSOECTs in more demanding applications.